Media framing of waste issues in selected Malaysian newspapers - Siti Aishah Chu, Abdullah@Vivian Chu Soo Lin; Hamidah, Abd Hamid (Universiti Teknikal Malaysia Melaka, 2010)
Human beings generate waste everyday in their lives. Due to population growth, improvements in standards of living and changing lifestyles of the people, more wastes will be generated. Hence, members of the public need to be informed, educated, acknowledged and reminded of their role to reduce wastes and to overcome waste problems. The media have a role as information transmitter and educator to the public; exposing and creating awareness among the public regarding environmental issues inclusive of waste control and management issues. This paper reports parts of a content analysis study which examined how environmental issues were covered and how waste issues were framed in selected Malaysian English-language newspapers. Articles regarding environmental issues published from January 2003 to December 2007 in The Sun and New Straits Times were analyzed. The study found 7,962 articles on environmental issues. Waste issues made up 7.7% of this coverage. For this paper, the 616 articles on waste issues were further examined to determine the presence of Entman’s (1993) four framing functions: to define problems, to diagnose causes, to make moral judgments, and to suggest solutions. Most prominent framing function was suggestion of solutions (47.1%) followed by problem definition (38%). Moral evaluations had the least presence with only 12.2%. The analysis also found another framing function: stating consequences in 34.9% of all waste articles. The paper concludes that media framing of waste issues in selected Malaysian newspapers focused on defining problems, stating consequences as well as suggesting solutions. Thus, media were to some extent performing the role of information transmitter and educator to the public.